Is the proteome of bronchoalveolar lavage extracellular vesicles a marker of advanced lung cancer? - Carvalho, Ana Sofia (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/).